Winning fixes everything : how baseball's brightest minds created sports' biggest mess - Drellich, Evan, 1987- (HarperCollins Publishers, 2023)
"The reporter who broke the Houston Astros' cheating scandal reveals how a baseball team could so dramatically descend into corruption, with never-before-told details of a broken management culture, the once-revered leaders who enabled it and the scandal itself." -- inside front jacket flap.